Current research in necrotizing enterocolitis. (June 2016) - Eaton, Simon; Rees, Clare M.; Hall, Nigel J.
Abstract: Despite decades of research on necrotizing enterocolitis, we still do not fully understand the pathogenesis of the disease, how to prevent or how to treat the disease. However, as a result of recent significant advances in the microbiology, molecular biology, and cell biology of the intestine of premature infants and infants with necrotizing enterocolitis, there is some hope that research into this devastating disease will yield some important translation into improved outcomes.